Digital tools for obtaining records, positioning and virtual articulation of casts - Díaz Díaz, Paula (2021)
The following literature review seeks to bring together the digital alternatives available for obtaining records, positioning and virtual articulation of models together with exemplifying some softwares to allow the implementation of these technologies in their daily workflow. A literature search was carried out in the following databases: Pubmed, LILACS, SciELO and Cochrane Library. Finally, after the results were filtered, a total of 36 publications were used. There are various tools currently available to digitize a large number of techniques that were only performed manually by an operator until a few years ago. Some of them facilitate a gradual immersion into the virtual world of the novice dentist since they lack high costs and resources. It is suggested that dentists implement these technologies into daily dental practice according to each particular case.